Theory and FDTD simulations of an amorphous silicon planar waveguide structure suitable to be used as a surface plasmon resonance biosensor - Fantoni, Alessandro (2020)
PTDC/NAN-OPT/31311/2017 UID/EEA/00066/2019 IPL/2018/aSiPhoto_ISEL AOP 2019, paper 28